Prevalence and Risk Factors of HIV Infection among Children Born from HIV Positive Women Musanze District, Rwanda - Nderelimana, Olivier; Muhimba, Innocent; Muhire, Philbert; Habtu, Micheal; Safari, Ennest; Rutayisire, Erigene (Journal of Public Health International, 2021)
In Rwanda the prevalence of mother-to-child HIV transmission is 1.5%, the prevalence was found to be higher in rural area. The purpose of this study was to determine the Prevalence and Risk Factors of HIV Infection among Children born from HIV Positive Women in Musanze District. The study findings help to decrease the rate of HIV infection among children born from mother HIV positive to zero. This study was conducted in Musanze District, Northern Province in Rwanda. The study targeted 420 HIV positive mothers who delivery in different health facilities located in Musanze district form January 2019 to December 2020 and their children. SPSS version 22 was used for analysis. Of 420 children born from HIV positive mothers 91.7% were aged between 18-24 months, 55.2% were female. The majority of HIV positive mothers 80.2% who participated in the study were married. The prevalence of HIV infection among children born from HIV positive women was 2.9%. Children whose mother had poor adherence to ART were 1.5 times more likely to get HIV at birth compared to those whose mother had good adherence (AOR = 1.5; 95% CI: (1.12-2.21)). Children born from mothers in WHO stage II were more likely to get HIV from their mother (AOR = 1.24; 95% CI: (1.32-2.207)). Children born from HIV positive mother with one ANC visit were 2.5 times more likely to get HIV from their mothers (AOR = 1.56; 95% CI: (2.31-5.17)).
Keywords: HIV Infection; Mother-to-Child Transmission; Children; Prevalence; Risk Factors; Rwanda